The Effects of Field Ridging and Flat-Field Planting on Growth and Yield of Three Legumes Grown Before Rice in the Pre-Monsoon Season of Northeastern Thailand - Polthanee, Anan (Agriculture and Natural Resources, 2001)
Field studies were conducted to assess the effects of field ridging and flat-field planting on the growth, yield and economic return of mungbean, cowpea and soybean grown before rice in the pre-monsoon season of Northeastern Thailand. The results showed that growth and yield of the 3 legumes were not significantly affected by field ridging. However, there was higher net income in flat-field planting treatments. This was attributed to high labour cost for ridge construction. Cowpea gave the highest seed yield with both field ridging and flat field planting treatments as compared with mungbean and soybean. In economic terms, however, soybean gave the maximum net return with flat-field planting treatments.